Divine Tobacco: A Paradox Among Health Fascism - Wempy Setyabudi Hernowo; M. Aufar Saputra Pratama Erawan (SOSIETAS, 2021)
This study aims to examine how ideally, the legal system regarding tobacco is related to the conflict of interest in tobacco use for the treatment. The type of research used in this research is normative legal research (normative juridical). Through a statutory approach and a conceptual approach, the aim is to understand the importance of using tobacco as an alternative treatment. By obtaining a clear concept, it is hoped that the norming in the rule of law in the future will no longer have a vague and ambiguous understanding.